Discussions that work - Ur, Penny (Cambridge University Press, 1981)
The first part provides some general guidelines on the organisation of successful task-centred activities. The second part consists of some fifty practical examples which have been tried and found effective in the classroom. They range from fairly simple to complex and sophisticated, and can thus be used with a wide range of learners, from elementary to the most advanced, in both secondary and adult education